2006
DOI: 10.1111/j.1572-0241.2005.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Fiber for the Treatment of Hemorrhoids Complications: A Systematic Review and Meta-Analysis

Abstract: Trials of fiber show a consistent beneficial effect for symptoms and bleeding in the treatment of symptomatic hemorrhoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(68 citation statements)
references
References 25 publications
1
51
0
13
Order By: Relevance
“…This is probably as fibre reduced constipation, which is one of the risk factors of hemorrhoids. 23 In the present study, author also found constipation to be one of the risk factors which was in accordance to other studies. 16,19,24 Straining during defecation was also found to be one of the risk factors which eventually resulted in complications such as bleeding through rectum, mass emerging through rectum as well as prolapse, which was also observed inpresent study.…”
Section: Discussionsupporting
confidence: 93%
“…This is probably as fibre reduced constipation, which is one of the risk factors of hemorrhoids. 23 In the present study, author also found constipation to be one of the risk factors which was in accordance to other studies. 16,19,24 Straining during defecation was also found to be one of the risk factors which eventually resulted in complications such as bleeding through rectum, mass emerging through rectum as well as prolapse, which was also observed inpresent study.…”
Section: Discussionsupporting
confidence: 93%
“…A consensus is emerging that a tailored approach is required for treatment of haemorrhoids based on grade. [92][93][94] Early-grade haemorrhoids can be effectively treated conservatively with diet, 95,96 alteration in lifestyle 94 and, perhaps, medical therapy, 38,97,98 whereas at the other end of the spectrum, grade IV circumferentially prolapsed piles may respond only to haemorrhoidectomy or SH. The eTHoS trial 99 hopes to provide data concerning the optimal procedure for the more advanced haemorrhoids.…”
Section: Justification Of Eligibility Criteriamentioning
confidence: 99%
“…Чем продолжительнее период родовой деятельно-сти, тем более выражены эти процессы. После родов проис-ходит постепенное сокращение сфинктера заднего прохо-да, внутренние узлы уменьшаются и самостоятельно вправ-ляются, но при быстром сокращении сфинктера возможно ущемление узлов и развитие острого геморроя [5,7,9].…”
Section: ключевые слова: геморрой лечение местная терапия постеризанunclassified